Cholesterol kinetics in subjects with bile fistula. Positive relationship between size of the bile acid precursor pool and bile acid synthetic rate - Schwartz, C C; Zech, L A; VandenBroek, J M; Cooper, P S (The Journal of clinical investigation, 1993)
Our aim was to identify and quantitate cholesterol pools and transport pathways in blood and liver. By studying bile fistula subjects, using several types of isotopic preparations, simultaneous labeling of separate cholesterol pools and sampling all components of blood and bile at frequent intervals, we developed a comprehensive multicompartmental model for cholesterol within the rapidly miscible pool. Data in six components (bile acids, esterified cholesterol in whole plasma, and free cholesterol in blood cells, bile, alpha lipoproteins, and beta lipoproteins) were modeled simultaneously with the SAAM program. The analysis revealed extensive exchange of free cholesterol between HDL and liver, blood cells, and other tissues. There was net free cholesterol transport from HDL to the liver in most subjects. The major organ that removed esterified cholesterol from blood was the liver. A large portion (4,211 mumol) of total hepatic cholesterol comprised a pool that turned over rapidly (t1/2 of 72 min) by exchanging mainly with plasma HDL and was the major source of bile acids and biliary cholesterol. Only 6% of hepatic newly synthesized cholesterol was used directly for bile acid synthesis: the analysis showed that 94% of newly synthesized cholesterol was partitioned into the large hepatic pool (putative plasma membrane free cholesterol) which exchanged rapidly with plasma lipoproteins. Bile acid synthetic rate correlated directly with the size of the large hepatic pool. In conclusion, hepatic and blood cholesterol pools and transports have been quantitated. HDL plays a central role in free cholesterol exchange/transport between all tissues and plasma. In humans, the metabolically active pool comprises a large portion of total hepatic cholesterol that, in part, regulates bile acid synthesis.